O PAPEL DO SINDICATO NA QUALIFICAÇÃO DA MÃO-DE-OBRA: SINDICATO-CIDADÃO - Ortiz, Paulo Henrique Falco (2009)
This paper deliberates about the importance of a new perspective on the defense of workers interests to the syndicates in Brazil, the citizen-syndicate (sindicatocidadão). The syndicalism in Brazil was born involved by a capitalist regime, going through a particular ideological process. In a country that the State has been keeping an indirect control over most syndicates, the most significant confronts were unexpressive, making in many cases, the workers lose the constant fight between work and capital. This loss is not only about money matters, but also, and even more important, about losses on the development of the worker in the technical level and, even more concerning, social levels. This paper has been suggested, to try to understand the role of syndicate entities on the recovery of workers strength, analyzing governmental qualification programs that were created by syndicate like entities. Data from PLANFOR, PNQ and Work s Caravan (caravana do trabalho) programs, from the São Paulo State government and also available information from the Studies and Research Institute of the Power Sector (IEPE -Instituto de Estudos e Pesquisas do Setor Energético), as the generating entity of qualification programs developed and financed by the State, using FAT resources. This analysis aims to detail, by a qualitative descriptive research, the necessities found on Government programs and also on Professional Qualification programs from IEPE besides an in depth interview with three syndicates Presidents. The information was gathered from secondary data from documents and bibliographical researches on public sources. This inquiry aimed to analyze if the programs meet people real needs and if more than just technically qualifying these people, promote citizenship notions. It was possible to understand that there are divergences about the real objective of the citizen-syndicate among interviewed people, probably making the qualification actions taken by the government and by the syndicate, vulnerable, becoming harder to reach the greater goal, which is the citizen-syndicate about, generating social insertion through qualification.(AU)